EKSISTENSI PLURALITAS DALAM PIAGAM MADINAH - Raihana (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2020)
The existence of plurality in the Medina Charter describes the plurality of the city of Medina, both topographically and socially, culturally, and religion which is marked by the existence of relations between Muslims and non-Muslims (Jews and Muslims) through a reciprocal agreement on the recognition of their respective religions. This shows the figure of the Prophet Muhammad SAW as a big siasiy (diplomat), wise in establishing community ties (republic / jumhuriyah) which are conditional with Islamic values. These Islamic values are implemented inclusively, including; the value of community equality and unity, freedom, religious tolerance, help, help, and defend the persecuted, deliberation, justice, equality of rights and obligations, neighborliness, defense and peace, amar makruf and nahi munkar, piety, and leadership.